Optical performance and corrosion resistance of TiN/Ni multiphase cermet by laser cladding. (November 2021) - Jiang, Jianxin; Pang, Xuming; Zhou, Jianxin; Li, Bin; Zhou, Fulin
Highlights: A laser cladding method was proposed to prepare the solar energy selective absorption coating. Single-layer and multi-phase cermet is found to have better optical properties. The single-layer TiN/TiC-based cermets coating has excellent the long-term thermal stability. The temperature field and dilution rate were researched by the theory and experiment. Abstract: Single-layer Ni-TiN cermet coating was prepared on the surface of stainless steel by spray method-laser cladding. The temperature field of the layer was researched. The reasonable parameters of the laser cladding were P = 900w, V = 3 mm/s, D = 3 mm. The results show that the simulated calculated process parameters are appropriate. In particular, an absorptance (α) of 76.4% and a thermal emissivity (ε) of 10% at 300 K were calculated when the weight rate of Ni/TiN is 1:1. After heat treatment at 650℃ for 200 h, the absorptance and emissivity of the coating were 78.8% and 5.2% respectively. The absorption rate and emissivity of the multiphase coating were 80.1% and 1.9%. Compared with the single-phase coating, the multiphase coating has better performance, good thermal stability at high temperature, and stable photothermal conversion efficiency.